Contrast induced nephropathy - Wan Ali, Wan Ahmad Syahril Rozli (2018)
Contrast nephropathy is a generally reversible form of acute kidney injury (AKI) that occurs soon after the administration of radiocontrast media. Although AKI is reversible in most cases, its development may be associated with adverse outcomes. The major clinical manifestations of contrast nephropathy are an increase in the serum creatinine and, less commonly, oliguria. Most patients are nonoliguric. The diagnosis of radiocontrast-induced nephropathy is based upon the clinical presentation, including the characteristic rise in serum creatinine concentration beginning with the first 24 to 48 hours after contrast exposure, and the exclusion of other causes of acute kidney injury (AKI). Dialysis is rarely required for acute kidney injury (AKI) following contrast administration.